Exploring the causal relationship between chronic periodontitis and oral cancer: An insight - Shaswata Karmakar; Baishakhi Modak; Monica Charlotte Solomon (Oral Oncology Reports)
Oral carcinoma is a major public health concern worldwide due to its increasing mortality. Apart from alcohol consumption, tobacco and areca nut chewing, other risk factors for oral cancer include chronic infection and inflammation, poor nutritional status, chronic trauma to the oral soft tissues etc. Risk of developing oral cancer increases with periodontal diseases. Induction of carcinoma by periodontal disease appears possible since the inflammatory mediators and bacterial toxins in the disease have a potential for malignant transformation. Establishing the etio-pathological connections between chronic periodontitis and oral carcinoma would be of great importance. Moreover, improvement of oral hygiene to prevent periodontal diseases also reduces the risks for cancer. These facts intensify the need for oral health education programs to educate individuals about the importance of maintaining a good oral hygiene for the early detection and prevention of oral cancer.